OS DESPROPÓSITOS DE UM MENINO-POETA: INFÂNCIA E POESIA EM MANOEL DE BARROS E MIA COUTO - Marques, Moama Lorena de Lacerda (Revista Crioula, 2012)
In this article we aim at doing a comparative analysis between the poem “O menino que carregava água na peneira” (The boy who carried water on a sive), by Manoel de Barros, and the short story “O menino que escrevia versos” (The boy who used to write verses), by Mia Couto, highlighting the construction of the relation between poetry and childhood. To achieve this, concerning the theoretical background, we base our work on the studies by Walter Benjamin, Freud, Sônia Kramer, Philippe Ariès, Antonio Candido, T.S. Eliot, among others.